A promising iPS-based single-cell cloning strategy revealing signatures of somatic mutations in heterogeneous normal cells - Miao, Xuexia (Comput Struct Biotechnol J, 2020)
Single-cell genomics has advanced rapidly as trace-DNA amplification technologies evolved. However, current technologies are subject to a variety of pitfalls such as contamination, uneven genomic coverage, and amplification errors. Even for the “golden” strategy of single stem cell-derived clonal formation, high-fidelity amplification is applicable merely to single stem cells. It’s still challenging to accurately define somatic mutations of a single cell in various cell types. Herein, we provided evidence, for the first time, to prove that induced pluripotent stem cells (iPS cells or iPSC), being a single somatic cell-derived clone, are recording almost identical (>90%) mutational profile of the initial cell progenitor. This finding demonstrates iPS technique, applicable to any cell type, can be utilized as a cell cloning strategy favorable for single-cell genomic amplification. This novel strategy is not limited by cell-type constraints or amplification artifacts, and thus enables our detailed investigation on the characteristics of somatic mutations in heterogeneous normal cells.